School society and pandemic in Mexico; online education: from temporary to permanent shelter - Gustavo Antonio Segura Lazcano; Ivett Vilchis Torres (Universidad de Guadalajara, 2021)
As a result of the global pandemic of covid-19, distance education went from being a little considered training option to the status of the main operating alternative for the school system. Educational institutions by adapting their work to the use of digital platforms have managed to keep their programs active despite reducing their training expectations. School activities at home face complex social situations that contravene the teaching precepts, cause poor learning and many cases of school dropout. Educational systems in the medium term will promote remote teaching modalities in digital and telematic versions, whose didactics will dominate the 21st century.